2020
DOI: 10.1155/2020/2061343
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Oil-Based Nanofluid as Next-Generation Insulation for Transformer Application

Abstract: Due to the increasing demand on developing good insulation, several researchers have performed experimental studies to prove the effectiveness and capabilities of transformer oil. This is done by suspending nanosized solid particles in the oil (nanofluid) for transformer applications. In brief, this paper presents a compilation of research studies which is divided into three parts. Part I discuss the preparation of the nanofluid which involves different types of nanomaterials, the optimal amount of concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 102 publications
0
21
0
Order By: Relevance
“…Bhatt and Bhatt [5] have reviewed the various studies done on electrical properties of transformer oil nanofluid and presented the summary of the review. Suhaimi et al [6] have reviewed and presented the synthesis of nanofluid, the effect of nanoparticles on the performance of dielectric strength of insulating liquid and limitations of Nanofluids to be avoided to make the nanofluid commercially available.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhatt and Bhatt [5] have reviewed the various studies done on electrical properties of transformer oil nanofluid and presented the summary of the review. Suhaimi et al [6] have reviewed and presented the synthesis of nanofluid, the effect of nanoparticles on the performance of dielectric strength of insulating liquid and limitations of Nanofluids to be avoided to make the nanofluid commercially available.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Characteristics of a good cooling liquid include high thermal conductivity, low viscosity, high specific heat, high dielectric strength (in case of direct liquid cooling), high surface tension, chemical inertness, chemical stability, low freezing point, and melting points, and low cost. Insulating liquids need to retain their electrical and thermo-physical properties for a long time [6]. But in practice, after using those oils for a long time they lose their properties.…”
mentioning
confidence: 99%
“…Many researchers have observed that the thermal conductivity enhancement along with rising temperature, regardless of the selection of nanomaterials, is due to the Brownian motion, where absorption of kinetic energy causes more particle collisions. However, the nanofluid's thermal performance generally would depend on the appropriate amount of concentrations of weight/volume percentages, which will jeopardize others [16]. One of the main objectives of this work is to analyze the influences of the Brownian microconvection and aggregation on the enhancement of the thermal conductivity of highly viscous liquids, as a function of the solid volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric strength (DS) of the insulating liquid is one of the most important factors in determining the reliability and durability of a transformer. It has been observed that the individual suspension of NPs can effectively slow down the streamer velocity and amplify the DS of the liquid dielectrics [1][2].…”
Section: Introductionmentioning
confidence: 99%